Potential therapeutic solution for Clostridioides difficile infection: Current scenario and future prospects - Chandrashekhar Singh; Anjali Singh; Deepjyoti Singh; Richa Upadhyay (Medicine in Microecology)
Clostridioides difficile previously known as Clostridium difficile is one of the three most potent human pathogens associated with antibiotic-associated diarrhoea and damage to the colon. Although advanced healthcare facilities with the development of new antibiotics are now available, these are associated with either treatment failure or disease recurrence. Any reason that disturbs the microbiome such as antibiotic treatment, unbalanced diet, stress and chronic disease may allow C. difficile, to adhere, colonize, grow and reproduce and eventually cause disease recurrence. With increasing knowledge about the natural defence mechanism of microbiome against gut pathogens, interest in non-antibiotic alternatives like prebiotics, synbiotics, probiotics, and postbiotics is quickly evolving. The gut microenvironment can be suitably modified by using prebiotics and probiotics either alone or by using their mixture as synbiotics. The gut microbiome prevents pathogen adhesion either by physical competition or by the proliferation of anti-inflammatory and antimicrobial products. Besides, there are other possible methods such as faecal matter transplantation (FMT) and microbiome replacement therapies (MRT) for the repopulation of the gastrointestinal tract. In this article, we review current treatment strategies for C. difficile infection (CDI) using prebiotics, probiotics, synbiotics, postbiotic FMT, and MRT. The article will give useful insight into the current therapies of CDI and their future developments.